Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian di E-Commerce Shopee : Studi Kasus Pada Mahasiswa di Kota Jambi - Hansen Rusliani; Syamsuddin Syamsuddin; Merdiana Ferdila (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of price, product quality and promotion on purchasing decisions at Shopee e-commerce. This research uses a quantitative approach with data collection methods through primary data, questionnaires and documentation. The population of this research are students at 10 universities in Jambi City and are Shopee e-commerce users. The total sample was 100 respondents. The sampling method uses a purposive sampling technique, namely a sampling technique using certain considerations that are in accordance with the researcher's objectives. The test used is multiple linear regression analysis; normality test, multicollinearity test and heteroscedasticity test. Test the hypothesis using the F Test and T Test. The results of data analysis can be concluded that partially (T test), the price variable (X1) has a significant effect on purchasing decisions (Y), the product quality variable (X2) has no effect on purchasing decisions (Y) and the promotion variable (X3) has an effect significant to purchasing decisions (Y). Simultaneously (F test) shows that the independent variables price, product quality and promotion simultaneously have a positive and significant effect on purchasing decisions.